2013
DOI: 10.1063/1.4816090
|View full text |Cite
|
Sign up to set email alerts
|

Role of point defects and HfO2/TiN interface stoichiometry on effective work function modulation in ultra-scaled complementary metal–oxide–semiconductor devices

Abstract: We investigate the physical properties of a portion of the gate stack of an ultra-scaled complementary metal-oxide-semiconductor (CMOS) device. The effects of point defects, such as oxygen vacancy, oxygen, and aluminum interstitials at the HfO2/TiN interface, on the effective work function of TiN are explored using density functional theory. We compute the diffusion barriers of such point defects in the bulk TiN and across the HfO2/TiN interface. Diffusion of these point defects across the HfO2/TiN interface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The material properties of ITO, TiN, and HfO2 used in these simulations are extracted from [32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…The material properties of ITO, TiN, and HfO2 used in these simulations are extracted from [32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, improving dielectric properties of thin gate dielectric and effective tuning work function are essential for reliable integration of MOS devices. Yet, as well known, proper tuning the EWF is still difficult because of its extreme sensitivity to many interfacial factors 7 , 8 . It has been reported that processing conditions of device may strongly affect the EWF 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although welldefined data for ALD STO/metal interfaces are not available from the literature, the ALD HfO 2 /metal system might serve as a reference here. For these interfaces, effective metal work functions of 5.15 eV for Pt 48 and (4.56 6 0.35) eV for TiN 49 in contact to ALD HfO 2 have been determined revealing a barrier offset of roughly 0.5 eV. From the 50% values of the CDF functions (Fig.…”
Section: Local Conductivity Probed By Lc-afmmentioning
confidence: 99%